THU0549 Fatigue and The Role of Sleep in fibromyalgia: Objective and Subjective Measures. (15th July 2016) - Guzzo, M.P.; Fernandes, M.; Iannuccelli, C.; Lucidi, F.; Mallia, L.; Lucchino, B.; Di Lollo, A.C.; Valesini, G.; Violani, C.; Di Franco, M.
Abstract : Background: Fibromyalgia (FM) is a chronic widespread pain syndrome associated with symptoms such as sleep disorders, fatigue, depression, anxiety and cognitive alterations with a severe impairment of the life quality. Objectives: The aim of this study is to examine the relationship between subjective and objective assessment of sleep quality and to analyze the predictors of fatigue in an Italian cohort of FM patients. Methods: Adult outpatients diagnosed with FM, fulfilling both ACR/EULAR 1990 and 2010 criteria were enrolled (1, 2). The objective measure of sleep was assessed through an actigraph (AMI Motionlogger Watch), a device which records the parameters of sleep based on electronic measure of the continuous motion detected by an accelerometer. During the study period the patients were invited to wear the actigraph on the non-dominant wrist for one week and concurrently to complete a sleep diary. After seven days the patients returned the actigraph and answered a structured interview conducted by a trained junior psychologist. Subjective quality of sleep was assessed by the Sleep Disorder Questionnaire (SDQ) (3) and the patients filled out psychometric scales as the Brief Symptom Inventory (BSI) for anxiety and depression (4) and the Checklist of Individual Strength (CIS20) for perceived fatigue (5). Both pharmacological and not pharmacological treatments were not changed 1 month before and during the study. Results: Twenty-one female patients completed the study, mean age of 46.9 years (range 32–68) and mean disease duration of 7.5 years (range 1–27). The majority of 21 FM patients interviewed (76.2%) described their sleep quality as poor or very poor (mean value 3.10 ±0.89 SD on 4 point Likert scale). All patients (100%) reported insomnia complaints, and 18 (81%) met the DSM V (Diagnostic and Statistical Manual of Mental Disorders) criteria for a diagnosis of Difficulties Initiating and Maintaining Sleep (DIMS). The patients' perception about the number of slept hours (M=5.7) was significantly lower (t=3.292, p<0.005) than the actigraphic data (M=6.8). Total Sleep Time (TST) measured through actigraphy was directly correlated with the intensity of perceived fatigue (r=.481; p<0.05). A multiple regression analysis considering TST, Total Time in Bed (TTB), depression, and type of fatigue self management, showed TST as the variable that gave a major and unique contribute to the prediction of perceived fatigue. Mean values of TST and TTB both negatively correlated with FM duration (respectively r=-.589, p<0.005; r=-.565, p<0.008). Conclusions: These findings confirm the high prevalence of sleep disturbances in FM and suggest that sleep quality and duration could play an important role in the perceived fatigue severity. Intervention programs for FM should include sleep regulation. References: Wolfe et al. Arthritis Care Res (Hoboken). 2010 Wolfe et al. Arthritis Rheum. 1990 Violani et al. Brain Research Bulletin 2004 Spence et al. Psychol Med. 2005 Beurskens et al. Occup Environ Med. 2000 Disclosure of Interest: None declared